PRO-INFLAMASI VERSUS ANTI-INFLAMASI SITOKIN: MITOS ATAU KENYATAAN - Pasaribu, Sumihar M. R. (Majalah Ilmiah METHODA, 2024)
Inflammation is characterized by interactions between pro- and anti-inflammatory cytokines. Cytokines are generally classified in one or another category: interleukin-1 (IL-1), tumor necrosis factor (TNF), gamma-interferon (IFN-γ), IL-12, IL-18 and granulocyte-macrophage colony-stimulating factor, . classified as pro-inflammatory cytokines while IL-4, IL-10, IL-13, IFN-α and transforming growth factor-β are anti-inflammatory cytokines. In this review, it is demonstrated that this classification is too simplistic and provides many examples illustrating that certain cytokines can behave as both pro- and anti-inflammatory cytokines. It is true, the amount of cytokines, the nature of the target cells, the nature of the activation signal, the nature of the cytokines produced, the timing, the order of action of the cytokines and even the experimental model are parameters that greatly influence the properties of the cytokines.